Mekanisme Dan Regulasi Hormon Glukokortikoid Pada Manusia - Lukman, Aprizal (Biospecies, 2008)
Glukokortikoid Hormone is produced by adrenal gland which is located at the end point of kidney anterior.This hormone contains 21 carbon atoms mainly aimed to boost up glukoneogenesis process. In human body,this hormone is usually called kortisol which is generated in fasciculate and glumerulosa zones